Chicken Feather Silage Meal As A Fish Meal Protein Source Replacement In Feed Formula Of Pomfret (Colossoma macropomum) - Arning Wilujeng Ekawati; Ating Yuniarti; Marsoedi Marsoedi (Research Journal of Life Science, 2016)
The research was conducted to know the effect and to determine the best utilization of the chiken feather silage meal as a substitute for fish meal protein source in the feed formula of Colossoma macropomum. This study used experimental method based on Completely Randomized Design (CRD) with 5 treatments and 3 replications. Five diets (33% isoprotein and 3.85 kcal/g diet isoenergi) were formulated with substitution of the chiken feather silage meal to fishmeal protein. These substituted 0, 25, 50, 75 and 100 % (A, B, C, D and E respectively) of the fishmeal protein. Parameters observed and analyzed were: survival rate, specific growth rate, feed conversion ratio, protein efficiency ratio, protein retention and protein digestibility. The results showed that the treatment had no effect on survival rate, specific growth rate, feed conversion ratio, protein efficiency ratio, and protein retention but the effect on protein digestibility. Based on these results, it can be concluded that fishmeal protein can be substituted with the chiken feather silage meal up to 100% in the feed formula of Colossoma macropomum.